Determinants Of Traffic Accident Occurrence Based On Road User Perceptions On The Rantepao-Pasar Bolu Corridor - Memed Timang Palembangan; Yulius Pakiding (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Traffic accidents remain a major challenge to transportation safety despite continuous improvements in road infrastructure. This study examined the determinants of traffic accident experience based on road users' perceptions of road safety along the Rantepao-Pasar Bolu corridor, North Toraja Regency, Indonesia. A quantitative survey was conducted with 60 respondents selected through accidental sampling. The study evaluated four perception variables: road surface condition, traffic signs and pavement markings, street lighting, and road user compliance. The questionnaire demonstrated acceptable validity (corrected item-total correlation = 0.49 - 0.66) and reliability (Cronbach's Alpha = 0.75). Data were analysed using descriptive statistics and binary logistic regression, while model performance was assessed using Nagelkerke R^2 and Receiver Operating Characteristic (ROC) analysis. The results showed that road surface condition received the highest mean score (4.15), whereas street lighting received the lowest (2.60). Street lighting was the only variable significantly associated with traffic accident experience (B = -1.353, p = 0.027, Exp(B) = 0.258), indicating that improved lighting reduced the likelihood of experiencing a traffic accident. The model explained 15.6% of the variation in accident experience (Nagelkerke R^2 = 0.156) and achieved acceptable discrimination (AUC = 0.714). These findings highlight the importance of improving street lighting to enhance road safety. Future research should include larger samples and additional explanatory variables to improve model performance.